Physical and Mechanical Properties of Autoclaved Aerated Concrete (AAC) as Partial Fine Aggregate in Concrete - Alik, Angelina Buhat Anak; A. Majid, Masni (Recent Trends in Civil Engineering and Built Environment, 2023)
Fine aggregate is the crucial component in the concrete production for construction projects. AAC is an eco-friendly and green building materials that is very sustainable. Nowadays, the uses of AAC in Malaysia is in a great demand due to rapid urbanization of development that needs to implement the quality of AAC aggregate properties Therefore, autoclaved aerated concrete (AAC) is used as the fine aggregate partial replacement in the concrete mixture. The main objective of this study is to determine the physical properties of concrete such as workability, density and mechanical properties such as compressive strength. The autoclaved aerated concrete (AAC) was crush to produce AAC aggregate as the partial sand replacement in concrete. Both properties of concrete will be tested. There were five concrete mixtures with AAC aggregates as the replacement of sand were prepared and tested. The mixture of concrete was partially replaced by 0%, 10%, 20, 30% and 40% of AAC aggregates with concrete grade of 30. A total of 30 specimens of concrete cubes with the dimension of 100mm × 100mm × 100mm were prepared and ready to be tested for the compressive strength after 7 and 28 days of curing. The compressive strength of concrete mix with autoclaved aerated concrete aggregate is higher at the specimen age of 28 days for it is the ideal design of concrete. The allowable addition of AAC aggregate in the concrete mix should not be greater than 20%. Besides, the optimum workability of concrete is at the range of 20 to 40% of AAC aggregate while the density is 2300kg/m3. Thus, the AAC is suitable to be used for replacing fine aggregate in producing of concrete due to its properties.